DNA methylation-mediated FGFR1 silencing enhances NF-κB signaling: implications for asthma pathogenesis - Meng, Minglu; Ma, Yingjiao; Xu, Jianguo; Chen, Gao; Mahato, Roshan Kumar (Frontiers in Molecular Biosciences, 2024)
Background: Fibroblast growth factor receptor 1 (FGFR1FGFR1) is known to play a crucial role in the pathogenesis of asthma, although the precise mechanism remains unclear. This study aims to investigate how DNA methylation-mediated silencing of FGFR1FGFR1 contributes to the enhancement of NF-κB signaling, thereby influencing the progression of asthma.Methods: RT-qPCR was utilized to assess FGFR1FGFR1 mRNA levels in the serum of asthma patients and BEAS-2B, HBEpiC, and PCS-301-011 cells. CCK8 assays were conducted to evaluate the impact of FGFR1FGFR1 overexpression on the proliferation of BEAS-2B, PCS-301-011, and HBEpiC cells. Dual-luciferase and DNA methylation inhibition assays were performed to elucidate the underlying mechanism of FGFR1FGFR1 gene in asthma. The MassARRAY technique was employed to measure the methylation levels of the FGFR1FGFR1 DNAgene.Results: Elevated FGFR1FGFR1 mRNA levels were observed in the serum of asthma patients compared to healthy controls. Overexpression of FGFR1FGFR1 in BEAS-2B cells significantly enhanced cell proliferation and stimulated NF-ĸB transcriptional activity in HERK-293T cells. Furthermore, treatment with 5-Aza-CdR, a DNA demethylating agent, markedly increased the expression of FGFR1FGFR1 mRNA in BEAS-2B, PCS-301-011, and HBEpiC cells. Luciferase activity analysis confirmed heightened NF-ĸB transcriptional activity in FGFR1FGFR1overexpressing BEAS-2B cells and BEAS-2B cells treated with 5-Aza-CdR. Additionally, a decrease in methylation levels in the FGFR1FGFR1 DNA promoter was detected in the serum of asthma patients using the MassARRAY technique.